2008
DOI: 10.2320/matertrans.mc200774
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Mechanical Properties of Mg-Al-Ca-Nd Alloys Fabricated by Gravity Casting and Extrusion Process

Abstract: The as-cast microstructure of Mg-5Al-3Ca-xNd alloys consists of equiaxed -Mg matrix, (Mg, Al) 2 Ca eutectic phase and Al-Nd rich intermetallic compounds. With the increase of Nd addition, -Mg matrix morphology was changed from dendritic to equiaxed grains due to suppression of grain growth by formation of homogeneous intermetallic compounds containing Nd dispersed at grain boundary and -Mg matrix. And the grain size of as-cast alloys was decreased as addition of Nd was increased. This eutectic phase of the ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…At 250°C, the ductility of all alloys was dramatically increased. In our previous study [8], dynamic recrystallized fine grains less than 4 µm were observed in all extruded Nd-containing alloys. It is natural to consider that the recrystallized fine grains were attributed to the occurrence of grain boundary sliding.…”
Section: Stress Mpamentioning
confidence: 58%
“…At 250°C, the ductility of all alloys was dramatically increased. In our previous study [8], dynamic recrystallized fine grains less than 4 µm were observed in all extruded Nd-containing alloys. It is natural to consider that the recrystallized fine grains were attributed to the occurrence of grain boundary sliding.…”
Section: Stress Mpamentioning
confidence: 58%
“…There are four major precipitation phases existing in the 0.7% Ca-AZ31: (Al,Mg) 2 Ca, β-Mg 17 Al 12 , Al 4 Mn and Φ-Mg 21 (Al,Zn) 17 . While β-Mg 17 Al 12 and Φ-Mg 21 (Al,Zn) 17 completely dissolves above approximately 450 K, (Al,Mg) 2 Ca remains stable up to 823 K, indicating that (Al,Mg) 2 Ca is the thermally stable phase. Figure 3 shows the backscattered phase is the most abundant phase.…”
Section: Microstructurementioning
confidence: 99%
“…For this reason, plastic deformation ability of the cast Mg-Al-Ca alloys is rather poor. Hot working, however, was shown to be able to improve the formability by effectively decreasing the grain size and fragmenting the coarse Al 2 Ca compounds into small particles [14][15][16][17][18][19]. The microstructure of the Mg-Ca-Al alloys [14][15][16][17][18] could be effectively refined by extrusion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the observation of microstructure, this is closely related to the number and size of the second phase. In addition, the literature shows that the Zn-modified samples increases the possibility of prismatic slip activation during deformation, which is beneficial to adjust the strain of grain c-axis, and can also inhibit grain boundary cracking to enhance grain boundary cohesion, thus greatly improving the plasticity of the alloy [38,39]. In the Cu-modified samples, Mg 2 Cu phase is formed, and the yield strength is increased by 19.5 MPa, compared with the TXZ311alloy, but the elongation is reduced to 8.89%, which is mainly due to the high hardness and modulus of Mg2Cu phase [40].…”
Section: Mechanical Property Analysismentioning
confidence: 99%